2016
DOI: 10.1371/journal.pone.0155033
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Candida within the Mycobiome/Microbiome of the Lower Respiratory Tract of ICU Patients

Abstract: Whether the presence of Candida spp. in lower respiratory tract (LRT) secretions is a marker of underlying disease, intensive care unit (ICU) treatment and antibiotic therapy or contributes to poor clinical outcome is unclear. We investigated healthy controls, patients with proposed risk factors for Candida growth in LRT (antibiotic therapy, ICU treatment with and without antibiotic therapy), ICU patients with pneumonia and antibiotic therapy and candidemic patients (for comparison of truly invasive and coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 53 publications
0
45
0
5
Order By: Relevance
“…Finally, in the only published study on pneumonia, which is the largest lung mycobiome study to date, Krause et al compared BAL from 87 healthy controls, 18 patients with extrapulmonary infection on antibiotics, 8 intensive care unit patients without antibiotics, 23 intensive care unit patients with extrapulmonay infection on antibiotics, 34 intensive care unit patients with pneumonia on antibiotics, and 32 patients with candidemia. 18 They focused on Candida and found that intensive care unit admission, but not antibiotic therapy, shifted the lung mycobiome to be dominated by Candida. Even this recent study still used culture-based fungal identification as the gold-standard for fungal identification, as this is standard practice in a clinical setting.…”
Section: What Do We Know About the Lung Mycobiome?mentioning
confidence: 99%
“…Finally, in the only published study on pneumonia, which is the largest lung mycobiome study to date, Krause et al compared BAL from 87 healthy controls, 18 patients with extrapulmonary infection on antibiotics, 8 intensive care unit patients without antibiotics, 23 intensive care unit patients with extrapulmonay infection on antibiotics, 34 intensive care unit patients with pneumonia on antibiotics, and 32 patients with candidemia. 18 They focused on Candida and found that intensive care unit admission, but not antibiotic therapy, shifted the lung mycobiome to be dominated by Candida. Even this recent study still used culture-based fungal identification as the gold-standard for fungal identification, as this is standard practice in a clinical setting.…”
Section: What Do We Know About the Lung Mycobiome?mentioning
confidence: 99%
“…However, the association was mainly derived from two patients with preceding antibiotic therapy and antifungal therapy and the contribution of fungal or bacterial microbiota to lung function could not be distinguished. Despite variable fungal composition in LRT, Candida overall dominated mycobiota in most of the studies including CF patients, lung transplant patients, HIV infected patients and ICU patients (Bousbia et al, 2012; Charlson et al, 2012; Bittinger et al, 2014; Willger et al, 2014; Cui et al, 2015; Kramer et al, 2015a; Krause et al, 2016). In remaining studies with dominating fungi other than Candida methodologies were too weak to draw profound conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In two previous studies reagents (e.g., saline, lab water, lab surfaces) have been analyzed to assess its influence on microbiota results from BAL (Bittinger et al, 2014; Krause et al, 2016); however, in other studies this was not done (Erb-Downward et al, 2011; van Woerden et al, 2011, 2013). Nevertheless, none of the studies investigating reagents showed that Candida abundance reached >50% as has been found in BAL samples from ICU patients (Krause et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations